Preparation method and test method of mussel adhesion-imitating self-healing hydrogel dressing
By preparing imitation mussels adhered to self-healing hydrogel dressings, the problems of structural damage and lack of adhesion under external forces are solved, and higher mechanical properties and adhesion are achieved, which extends the Lifespan and avoid wound infection.
Patent Information
- Application Number
- CN202411422105.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional hydrogel dressings are prone to structural damage when subjected to external forces, affecting their effect, increasing the number of replacements, and even causing wound infection. At the same time, they lack adhesion and need to be fixed with the help of external objects, resulting in poor contact with the fixing interface, which can easily cause wound infection. .
Using the preparation method of imitation mussel-adhesive hydrogel dressing, oxidized hyaluronic acid is synthesized by hyaluronic acid and sodium periodate, and self-healing water is prepared based on Schiff base reaction with carboxymethyl chitosan Gel, add polydopamine-modified bacterial cellulose to enhance adhesion and mechanical properties.
It improves the mechanical properties and adhesion of the dressing, and can self-heal after being damaged by external forces, reduces the number of replacements, extends the service life, and avoids wound infection.
Smart Images

Figure CN119455069A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wound dressings, and in particular to a preparation method and a testing method of a mussel-imitation adhesion self-healing hydrogel dressing. Background Art
[0002] Due to factors such as the constant movement of the body, skin tissue is often damaged and even a large wound surface is formed, which needs to be repaired. During the wound repair process, microorganisms can easily invade the wound and form bacterial colonies at the wound site, leading to serious wound infection.
[0003] Clinically, an ideal dressing should help accelerate wound healing and act as an antibiotic to prevent wound infection. Compared with traditional dressings such as dressings, bandages, gauze, etc., hydrogel dressings have greater advantages in clinical applications due to their high water content and good biocompatibility. Now, many natural and synthetic polymers, such as peptides, gelatin, chitosan and polysaccharides, have been used in hydrogel dressings, and many hydrogel dressings have been used in wound care and anti-infection clinical diagnosis.
[0004] However, when subjected to external forces, the structure of traditional hydrogel dressings may be destroyed, which in turn affects the effect of the hydrogel dressings, increases the number of dressing changes, and even causes wound infection. In addition, traditional hydrogel dressings need to be fixed to the skin wound with the help of external objects such as tape, and poor contact at the fixed interface can easily cause wound infection. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and a testing method of a mussel-like self-healing hydrogel dressing, so as to solve the problem that the structure of the traditional hydrogel dressing may be destroyed when subjected to external force, thereby affecting the effect of the hydrogel dressing, increasing the number of dressing changes, shortening the dressing life cycle, and even causing wound infection. At the same time, it solves the problem that the traditional hydrogel dressing has no adhesion and needs to be fixed to the skin wound with the help of external objects such as tape, and the poor contact of the fixed interface is also prone to cause wound infection.
[0006] To achieve the above object, the present invention provides a preparation method and a testing method of a mussel-mimicking self-healing hydrogel dressing. The preparation method of the mussel-mimicking self-healing hydrogel dressing comprises the following steps:
[0007] S1: Synthesis of oxidized hyaluronic acid using hyaluronic acid and sodium periodate;
[0008] S2: adding dopamine hydrochloride to the bacterial cellulose suspension, adjusting the pH to 12 with sodium hydroxide, and stirring, DA polymerizes in an alkaline environment to obtain a polydopamine-modified bacterial cellulose suspension for use;
[0009] S3: preparing a self-healing hydrogel by reacting the prepared oxidized hyaluronic acid with carboxymethyl chitosan based on Schiff base;
[0010] S4: Based on nano-enhancement and mussel-like adhesion mechanism, polydopamine-modified bacterial cellulose was added to the prepared self-healing hydrogel to obtain a mussel-like adhesion self-healing hydrogel dressing.
[0011] The method for preparing the mussel-mimicking self-healing hydrogel dressing further includes preliminary preparations, which include:
[0012] Dispersion of bacterial cellulose: accurately weigh 4 g of bacterial cellulose and rinse it with secondary water, cut it into pieces and put it into a 100 mL beaker, add 50 mL of ultrapure water to dissolve it, and use an ultrasonic crusher to crush and disperse it to obtain an 8% w / v BC bacterial cellulose suspension for use;
[0013] Preparation of 3 mol / L NaOH solution: weigh 12 g of sodium hydroxide solid, dissolve it twice in a beaker, drain it into a 100 mL volumetric flask with a glass rod and dilute to the mark, then shake well for later use;
[0014] Preparation of 3 mol / L HCL solution: Use a measuring cylinder to measure 25 mL of 36% hydrochloric acid and pour it into a beaker. Dissolve it with distilled water and drain it into a 100 mL volumetric flask with a glass rod and dilute to the mark. Shake well and set aside.
[0015] Preparation of hydroxylamine hydrochloride-methyl orange solution: weigh 0.025g of methyl orange powder in a beaker and add 50mL of deionized water to dissolve it to obtain a 0.05% w / v methyl orange aqueous solution for later use; accurately weigh 4.34g of hydroxylamine hydrochloride, add 200mL of deionized water to fully dissolve it in a beaker, pour the beaker solution into a 250mL volumetric flask and add 2.5mL of 0.05% w / v methyl orange aqueous solution and dilute to the scale line for later use.
[0016] Wherein, step S1 is specifically as follows:
[0017] Weigh 2 g of hyaluronic acid and dissolve it in 200 mL of deionized water. Stir and dissolve it at 25°C to obtain a 1% w / v hyaluronic acid aqueous solution. Dissolve 1.27 g of sodium periodate in 20 mL of deionized water under light-protected conditions.
[0018] In a light-proof environment, add sodium periodate aqueous solution dropwise into the hyaluronic acid solution, and react in a light-proof environment at 25°C for 8 hours. Then, add 1 mL of ethylene glycol to the solution and continue stirring for 1 hour to terminate the oxidation reaction.
[0019] To obtain a pure product, the product was dialyzed for 3 days using a 3.5 KDa dialysis bag and freeze-dried to obtain oxidized hyaluronic acid.
[0020] Wherein, in step S1, the molar ratio of sodium periodate:hyaluronic acid is 1.2:1.
[0021] Among them, the specific steps of step S2 are: weigh a preset mass of dopamine hydrochloride and add it to 10mL of 8% w / v bacterial cellulose suspension, and adjust the pH to 12 with 3 mol / L sodium hydroxide, stir with a magnetic stirrer for 1 hour under open room temperature environment, DA polymerizes in an alkaline environment, and obtains a polydopamine-modified bacterial cellulose suspension for use.
[0022] Wherein, in step S3, the concentration of carboxymethyl chitosan is 4% w / v, and it is transparent and viscous, and the concentration of oxidized hyaluronic acid is 10% w / v, and its aqueous solution is transparent water.
[0023] The present invention also provides a test method for a mussel-like self-healing hydrogel dressing, which is applied to the mussel-like self-healing hydrogel dressing prepared by the preparation method of the mussel-like self-healing hydrogel dressing as described above, and includes the following test contents:
[0024] The hydroxylamine hydrochloride method was used to quantitatively determine the amount of aldehyde groups in the modified hyaluronic acid;
[0025] Test on gelation time of mussel-mimicking self-healing hydrogel dressing;
[0026] Mechanical properties testing of mussel-mimicking self-healing hydrogel dressing;
[0027] Adhesion ability and adhesion strength test of mussel-mimicking self-healing hydrogel dressing;
[0028] SEM test of mussel-mimicking self-healing hydrogel dressing;
[0029] Swelling property test of mussel-mimicking self-healing hydrogel dressing;
[0030] Testing the self-healing ability of mussel-mimicking self-healing hydrogel dressing;
[0031] Drug release test of mussel-mimicking self-healing hydrogel dressing;
[0032] Test of the antibacterial ability of mussel-mimicking self-healing hydrogel dressing.
[0033] The specific test steps for quantitatively determining the amount of aldehyde groups in modified hyaluronic acid using the hydroxylamine hydrochloride method are as follows:
[0034] Weigh 0.025 g of methyl orange powder in a beaker and add 50 mL of deionized water to dissolve it to obtain a 0.05% w / v methyl orange aqueous solution for later use; accurately weigh 4.34 g of hydroxylamine hydrochloride and add 200 mL of deionized water to fully dissolve it in a beaker; pour the beaker solution into a 250 mL volumetric flask and add 2.5 mL of 0.05% w / v methyl orange aqueous solution and dilute to the scale for later use;
[0035] Weigh 0.1g of oxidized hyaluronic acid and add 25mL of hydroxylamine hydrochloride-methyl orange solution. Dissolve under magnetic stirring and leave for 3h. Titrate with 0.01mol / L sodium hydroxide solution and the color changes from red to yellow. The volume of sodium hydroxide consumed is recorded as V and the volume of blank control is recorded as V 0 ;
[0036] The oxidation degree and aldehyde content are calculated according to the following formula:
[0037]
[0038]
[0039] Where n NaOH is the molar concentration of NaOH used for titration, in mol / L; W OHA is the mass of the sample measured, in g.
[0040] Among them, the specific test method for the mechanical properties test of the mussel-like self-healing hydrogel dressing is:
[0041] The compression performance of the mussel-like self-healing hydrogel dressing samples was tested using a universal mechanical machine, and the compression speed was set to 5 mm / min;
[0042] The stress calculation formula is:
[0043]
[0044] The strain calculation formula is:
[0045]
[0046] Where Load is the load value, unit is N; position is the displacement, unit is mm.
[0047] Among them, the specific test method for the swelling performance test of the mussel-like self-healing hydrogel dressing is:
[0048] The hydrogels prepared under different conditions were immersed in PBS solution and the temperature was set at 37°C. The hydrogels were taken out from PBS every 4 hours to remove the surface water and then weighed and recorded as W. t , the initial weight of the hydrogel is recorded as W 0, the swelling rate test formula is: swelling rate (%) = W t / W 0 ×100%.
[0049] Among them, the specific test steps for the antibacterial ability test of the mussel-like self-healing hydrogel dressing are as follows:
[0050] Use a hole puncher to punch the common filter paper used in the laboratory into discs with a diameter of 0.5 cm, put them in a test tube, seal and sterilize;
[0051] Prepare a suspension of the cultured E. coli at a preset concentration, use a pipette to draw 2 mL of the bacterial suspension into a sterilized culture dish, rotate the culture dish to mix the culture medium and bacterial solution, and let it stand to form a plate;
[0052] Use a pipette to draw 15 μL of sterile water, pick up a piece of filter paper with sterile tweezers, soak the filter paper with sterile water, and gently stick the filter paper on the culture medium as a blank control;
[0053] Use tweezers to pick up the hydrogel and gently stick it on the culture medium. Repeat the experiment for each sample in triplicate according to the above method, and use a filter paper soaked in sterile water as a blank control.
[0054] After incubation at 37°C for a preset time, observe and measure the size of the inhibition zone with a ruler or vernier caliper to calculate the inhibition rate.
[0055] The invention discloses a preparation method and a testing method of a mussel-like adhesion self-healing hydrogel dressing. Biocompatible carboxymethyl chitosan and oxidized hyaluronic acid with excellent water absorption and water locking effects are selected to prepare a self-healing hydrogel based on a Schiff base reaction. Based on nano-enhancement and a mussel-like adhesion mechanism, polydopamine-modified bacterial cellulose is added to prepare a mussel-like adhesion self-healing hydrogel dressing. Compared with traditional hydrogel dressings, the prepared mussel-like adhesion self-healing hydrogel dressing has excellent mechanical properties and adhesion, and can self-heal after being damaged by external force, thereby reducing the number of dressing changes, extending the service life of the dressing and avoiding wound infection. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0057] Figure 1 The present invention is a flowchart of the steps of the method for preparing the mussel-mimicking adhesion self-healing hydrogel dressing provided by the present invention.
[0058] Figure 2 It is a synthesis equation diagram of the oxidized hyaluronic acid provided by the present invention.
[0059] Figure 3 It is a schematic diagram of the gelation process of the preparation process of polydopamine-modified bacterial cellulose provided by the present invention.
[0060] Figure 4 It is a schematic diagram of gelation time in the preparation process of polydopamine-modified bacterial cellulose provided by the present invention.
[0061] Figure 5 It is a schematic diagram of the stress-strain curve and elastic modulus of the self-healing hydrogel provided by the present invention.
[0062] Figure 6 It is a schematic diagram of the stress-strain curve of the control group hydrogel and the elastic modulus of the control group hydrogel provided by the present invention.
[0063] Figure 7 It is a schematic diagram of the stress-strain curve of the mussel-mimicking self-healing hydrogel and the elastic modulus of the mussel-mimicking self-healing hydrogel provided by the present invention.
[0064] Figure 8 It is a schematic diagram of the mussel-mimicking self-healing hydrogel provided by the present invention adhering to the surfaces of various materials.
[0065] Fig. 9 It is a schematic diagram of the adhesion strength test results of the mussel-mimicking self-healing hydrogel dressing provided by the present invention on a glass slide.
[0066] Fig.10 This is a SEM morphology picture of the mussel-mimicking self-healing hydrogel dressing provided by the present invention.
[0067] Fig.11 It is a swelling curve diagram of the mussel-mimicking self-healing hydrogel dressing provided by the present invention.
[0068] Fig.12 This is a self-healing observation diagram of the mussel-mimicking self-healing hydrogel dressing provided by the present invention.
[0069] Fig.13 It is a drug-loading release curve diagram of the mussel-mimicking adhesion self-healing hydrogel dressing provided by the present invention.
[0070] Fig.14 It is a comparison diagram of the sizes of the antibacterial zones in the antibacterial test of the mussel-mimicking self-healing hydrogel dressing provided by the present invention. DETAILED DESCRIPTION
[0071] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0072] See also Figure 1 The present invention provides a preparation method and a testing method of a mussel-like self-healing hydrogel dressing. The preparation method of the mussel-like self-healing hydrogel dressing comprises the following steps:
[0073] S1: Synthesis of oxidized hyaluronic acid using hyaluronic acid and sodium periodate;
[0074] S2: adding dopamine hydrochloride to the bacterial cellulose suspension, adjusting the pH to 12 with sodium hydroxide, and stirring, DA polymerizes in an alkaline environment to obtain a polydopamine-modified bacterial cellulose suspension for use;
[0075] S3: preparing a self-healing hydrogel by reacting the prepared oxidized hyaluronic acid with carboxymethyl chitosan based on Schiff base;
[0076] S4: Based on nano-enhancement and mussel-like adhesion mechanism, polydopamine-modified bacterial cellulose was added to the prepared self-healing hydrogel to obtain a mussel-like adhesion self-healing hydrogel dressing.
[0077] In this embodiment, biocompatible carboxymethyl chitosan and oxidized hyaluronic acid with excellent water absorption and water locking effects are selected to prepare self-healing hydrogel based on Schiff base reaction, and based on nano-enhancement and mussel-like adhesion mechanism, polydopamine-modified bacterial cellulose is added to prepare mussel-like adhesion self-healing hydrogel dressing. Compared with traditional hydrogel dressings, the prepared mussel-like adhesion self-healing hydrogel dressing has stronger mechanical properties and adhesion, and can self-heal after being damaged by external force, thereby reducing the number of dressing changes, extending the service life of the dressing and avoiding wound infection.
[0078] Among them, carboxymethyl chitosan can be referred to as CMCS, hyaluronic acid can be referred to as HA, oxidized hyaluronic acid can be referred to as OHA, bacterial cellulose can be referred to as BC, polydopamine-modified bacterial cellulose can be referred to as BC-PDA, self-healing hydrogel can be referred to as OHA-CMCS, and mussel-mimicking self-healing hydrogel dressing can be referred to as OHA-CMCS / BC-PDA.
[0079] Furthermore, the preparation method of the mussel-mimicking self-healing hydrogel dressing also includes preliminary preparations, which include:
[0080] Dispersion of bacterial cellulose: accurately weigh 4 g of bacterial cellulose and rinse it with secondary water, cut it into pieces and put it into a 100 mL beaker, add 50 mL of ultrapure water to dissolve it, and use an ultrasonic crusher to crush and disperse it to obtain an 8% w / v BC bacterial cellulose suspension for use;
[0081] Preparation of 3 mol / L NaOH solution: weigh 12 g of sodium hydroxide solid, dissolve it twice in a beaker, drain it into a 100 mL volumetric flask with a glass rod and dilute to the mark, then shake well for later use;
[0082] Preparation of 3 mol / L HCL solution: Use a measuring cylinder to measure 25 mL of 36% hydrochloric acid and pour it into a beaker. Dissolve it with distilled water and drain it into a 100 mL volumetric flask with a glass rod and dilute to the mark. Shake well and set aside.
[0083] Preparation of hydroxylamine hydrochloride-methyl orange solution: weigh 0.025g of methyl orange powder in a beaker and add 50mL of deionized water to dissolve it to obtain a 0.05% w / v methyl orange aqueous solution for later use; accurately weigh 4.34g of hydroxylamine hydrochloride, add 200mL of deionized water to fully dissolve it in a beaker, pour the beaker solution into a 250mL volumetric flask and add 2.5mL of 0.05% w / v methyl orange aqueous solution and dilute to the scale line for later use.
[0084] Furthermore, step S1 is specifically as follows:
[0085] Weigh 2 g of hyaluronic acid and dissolve it in 200 mL of deionized water. Stir and dissolve it at 25°C to obtain a 1% w / v hyaluronic acid aqueous solution. Dissolve 1.27 g of sodium periodate in 20 mL of deionized water under light-protected conditions.
[0086] In a light-proof environment, add sodium periodate aqueous solution dropwise into the hyaluronic acid solution, and react at 25°C in a light-proof environment for 8 hours. Then, add 1 mL of ethylene glycol to the solution and continue stirring for 1 hour to terminate the oxidation reaction.
[0087] To obtain a pure product, the product was dialyzed for 3 days using a 3.5 KDa dialysis bag and freeze-dried to obtain oxidized hyaluronic acid.
[0088] Among them, the synthesis equation of oxidized hyaluronic acid is as follows Figure 2 As shown, the molar ratio of sodium periodate:hyaluronic acid = 1.2:1.
[0089] Furthermore, the specific steps of step S2 are: weigh a preset mass of dopamine hydrochloride and add it to 10mL of 8% w / v bacterial cellulose suspension, and adjust the pH to 12 with 3 mol / L sodium hydroxide, stir with a magnetic stirrer for 1 hour at room temperature, and polymerize DA in an alkaline environment to obtain a polydopamine-modified bacterial cellulose suspension for use.
[0090] In this embodiment, the pH of the suspension after 1 hour of reaction was adjusted to a neutral environment with 3 mol / L HCL to terminate the continued polymerization of DA, and the suspension without termination of the reaction was set as a control group. The ratio of BC to DA and the grouping of whether the experimental reaction was terminated after 1 hour are shown in Table 1:
[0091] Table 1. Preparation of BC-PDA
[0092]
[0093] Furthermore, in step S3, the concentration of carboxymethyl chitosan is 4 wt %, and it is transparent and viscous; the concentration of oxidized hyaluronic acid is 10 wt %, and its aqueous solution is transparent and watery.
[0094] In this embodiment, in order to explore the mechanical strength of oxidized hyaluronic acid-carboxymethyl chitosan hydrogels with different ratios, the technical scheme prepares self-healing hydrogels with volume ratios of oxidized hyaluronic acid to carboxymethyl chitosan solution of 1:1, 1:3, 1:5 and 1:7 respectively.
[0095] Furthermore, in order to avoid excessive polymerization of DA leading to decreased adhesion, the present technical solution designed a termination and non-termination experiment after 1h of BC-PDA reaction. The experiment was divided into 7 groups, and the hydrogel without BC-PDA was defined as No. 1, and the hydrogels with different preparation conditions and different volumes of BC-PDA were defined as No. 2, 3, 4, 5, 6, and 7. The hydrogels with only BC and PDA were set as the control group, among which, the hydrogels No. 2-7 were all tested with the addition of terminated and non-terminated BC-PDA, as shown in Table 2:
[0096] Table 2. Experimental groups
[0097]
[0098] The present invention also provides a test method for a mussel-like self-healing hydrogel dressing, which is applied to the mussel-like self-healing hydrogel dressing prepared by the preparation method of the mussel-like self-healing hydrogel dressing as described above, and includes the following test contents:
[0099] The hydroxylamine hydrochloride method was used to quantitatively determine the aldehyde content of modified hyaluronic acid;
[0100] Test on gelation time of mussel-mimicking self-healing hydrogel dressing;
[0101] Mechanical properties testing of mussel-mimicking self-healing hydrogel dressing;
[0102] Adhesion ability and adhesion strength test of mussel-mimicking self-healing hydrogel dressing;
[0103] SEM test of mussel-mimicking self-healing hydrogel dressing;
[0104] Swelling property test of mussel-mimicking self-healing hydrogel dressing;
[0105] Testing the self-healing ability of mussel-mimicking self-healing hydrogel dressing;
[0106] Drug release test of mussel-mimicking self-healing hydrogel dressing;
[0107] Test of the antibacterial ability of mussel-mimicking self-healing hydrogel dressing.
[0108] The specific test steps for quantitatively determining the amount of aldehyde groups in modified hyaluronic acid using the hydroxylamine hydrochloride method are as follows:
[0109] Weigh 0.025 g of methyl orange powder in a beaker and add 50 mL of deionized water to dissolve it to obtain a 0.05% w / v methyl orange aqueous solution for later use; accurately weigh 4.34 g of hydroxylamine hydrochloride and add 200 mL of deionized water to fully dissolve it in a beaker; pour the beaker solution into a 250 mL volumetric flask and add 2.5 mL of 0.05% w / v methyl orange aqueous solution and dilute to the scale for later use;
[0110] Weigh 0.1g of oxidized hyaluronic acid and add 25mL of hydroxylamine hydrochloride-methyl orange solution. Dissolve under magnetic stirring and leave for 3h. Titrate with 0.01mol / L sodium hydroxide solution and the color changes from red to yellow. The volume of sodium hydroxide consumed is recorded as V and the volume of blank control is recorded as V 0 ;
[0111] The oxidation degree and aldehyde content are calculated according to the following formula:
[0112]
[0113] Where n NaOH is the molar concentration of NaOH used for titration, in mol / L; W OHA is the mass of the sample measured, in g.
[0114] In this embodiment, the aldehyde group on the oxidized hyaluronic acid can react with the primary amine group quickly through the Schiff base reaction to form a self-healing hydrogel. The degree of oxidation of HA can be controlled by controlling the molar ratio of hyaluronic acid to sodium periodate and the reaction time. The NaOH consumption is 13.5 mL and the aldehyde content is 0.067 mmol by the hydroxylamine hydrochloride titration method. The degree of oxidation of the modified OHA is calculated to be 27%, as shown in Table 3:
[0115] Table 3. Aldehyde content test
[0116]
[0117]
[0118] Further, such as Figure 3 and Figure 4 As shown, the specific results of the gelation time test of the mussel-like self-healing hydrogel dressing are as follows:
[0119] The flake BC was dispersed into a uniform suspension using an ultrasonic cell disruptor, and DA monomer was added to the BC dispersion to polymerize in an alkaline environment to obtain BC-PDA polymer. As the reaction time increased, the color of the BC-PDA solution gradually deepened from white ( Figure 3 a in the figure) turns brown ( Figure 3 b), and eventually turns dark brown ( Figure 3 As shown in d), it proves that DA is successfully polymerized into PDA. CMCS and OHA generate the first layer of network through Schiff base reaction, CMCS / OHA and BC-PDA further enhance the mechanical properties of hydrogel through hydrogen bonding, and after the solution is inverted in the vial for 8 minutes, the solution no longer flows, indicating the formation of mussel-like nano-enhanced self-healing hydrogel;
[0120] The results of determining the hydrogel gelation time by tilting and inverting the mold are as follows Figure 4 As shown in the figure, with the increase of BC-PDA content, the gelation speed slows down significantly. At the same time, the gelation time of BC-PDA hydrogel prepared by the termination reaction is shorter than that of BC-PDA hydrogel prepared by the unterminated reaction. This is because the hydroxyl groups on the unterminated BC-PDA are over-oxidized, and the cross-linking points with the hydroxyl groups, amino groups and other groups on the side chains of OHA and CMCS are reduced, and the gelation is slow. When the same volume of BC-PDA is added, the gelation time (5min) of the hydrogel with 10μL BC-PDA (8:1) is lower than the gelation time (7min) of the hydrogel with 10μL BC-PDA (4:1). This is because the cross-linking points with the hydroxyl groups, amino groups and other groups on the side chains of OHA and CMCS are reduced after the high content of DA is over-oxidized, and the gelation is slowed down.
[0121] Furthermore, the specific test method for the mechanical properties test of the mussel-like self-healing hydrogel dressing is as follows:
[0122] The compression performance of the mussel-like self-healing hydrogel dressing samples was tested using a universal mechanical machine, and the compression speed was set to 5 mm / min;
[0123] The stress calculation formula is:
[0124]
[0125] The strain calculation formula is:
[0126]
[0127] Where Load is the load value, unit is N; position is the displacement, unit is mm.
[0128] In this embodiment, Figures 5 to 7 It can be seen that by changing the ratio of CMCS to OHA, self-healing hydrogels with different ratios were prepared. As the CMCS content increased, the stress and elastic modulus that the self-healing hydrogel could withstand increased accordingly. The best value was reached when OHA:CMCS=1:7, and the elastic modulus was 33.72KPa. As the CMCS content increased, the degree of binding between the aldehyde group in OHA and the amino group in CMCS increased, which improved the mechanical properties of the OHA-CMCS self-healing hydrogel;
[0129] Analysis of the control group hydrogels with only PDA and BC added: After adding a certain amount of PDA, the stress and elastic modulus that the hydrogel can withstand remained basically unchanged. After adding a certain amount of BC, the stress and elastic modulus that the hydrogel can withstand were significantly enhanced. After adding 20μL 8%wt BC, the elastic modulus of the hydrogel reached 59.42KPa, which is 1.8 times that of the OHA-CMCS hydrogel. After adding 20μL BC-PDA (8:1, under termination preparation conditions), the elastic modulus reached 119.71KPa, which is much higher than the elastic modulus of the self-healing hydrogel with only 20μLPDA, 20μLBC and OHA-CMCS. This is because the large number of hydroxyl groups on the side chains of BC-PDA can form a large number of hydrogen bonds with hydroxyl groups, amino groups and other groups on OHA / CMCS, thereby enhancing the mechanical strength of the gel;
[0130] OHA:CMCS=1:7 was selected as the first layer network, and different BC:DA ratios and different contents of BC-PDA were added to prepare hydrogels and perform compression tests. The terminated reaction and the unterminated reaction were compared. The results are shown in Figure 7As shown. The results show that when BC:PDA is 8:1, the mechanical properties of the hydrogels are improved after adding BC-PDA, whether terminated or not. This is due to the unique fibrous network structure of BC, which gives the hydrogels super strong mechanical strength through hydrogen bonding in the hydrogel network. When the amount of BC-PDA added is 60μL, its elastic modulus increases to 210.39KPa (unterminated) and 247.75KPa (terminated), which is 6.2 times or even 7.3 times that of OHA-CMCS self-healing hydrogels. The results show that adding BC-PDA complexes is a good way to enhance the mechanical properties of hydrogels. Secondly, when the BC-PDA preparation condition is 4:1, the elastic modulus of the hydrogels after adding 10μL and 20μL BC-PDA is also significantly improved compared with the OHA-CMCS self-healing hydrogel, reaching 73.62KPa and 105.64KPa. However, it is lower than that of adding 10μL and 20μL BC-PDA (8:1). This may be because the excessive polymerization of DA monomer under 4:1 conditions will lead to excessive oxidation of the catechol groups on DA, reducing the formation of hydrogen bonds with hydroxyl, amino and other groups on OHA / CMCS and reducing the mechanical strength.
[0131] Finally, in all the comparative experimental groups, the mechanical properties of BC-PDA after termination reaction were higher than those of BC-PDA without termination. Therefore, combined with the gelation time and mechanical properties test results, the OHA-CMCS / BC-PDA mussel adhesion self-healing hydrogel prepared under termination reaction conditions was used for other tests in subsequent experiments.
[0132] Furthermore, the test method for the adhesion ability and adhesion strength test of the mussel-like self-healing hydrogel dressing is as follows:
[0133] The catechol groups in polydopamine can provide super strong adhesion to various substrate materials. Therefore, OHA-CMCS / BC-PDA hydrogel has excellent adhesion to various material surfaces, including hydrophilic and hydrophobic surfaces. Figure 8 As shown, the hydrogel can be tightly attached to latex gloves (such as Figure 8 a), glass bottle cap filled with water (as shown in Figure 8 b), centrifuge tube (as shown in Figure 8 c) and brown glass bottles (as Figure 8 d) without falling off. The hydrogel is adhered between two smooth glass slides, and a 50g weight (as shown in Figure 8 e) and a 360 g rubber stopper (as Figure 8 f).
[0134] The hydrogel precursor solution was evenly applied on two glass slides. After 2 hours, the adhesion strength was tested using a universal mechanical testing machine. The results are as follows: Fig. 9As shown. The adhesion strength of OHA-CMCS self-healing hydrogel is low, only 2.63KPa. After adding PDA, the adhesion strength is significantly increased to 4.96KPa. Due to the non-covalent and covalent "anchoring" effect of the catechol groups on PDA and the surface of foreign bodies, and the formation of "catechol-catechol" covalent cross-linking bonds, the hydrogel has a tough and durable adhesion to various foreign surfaces. Whether it is the BC-PDA (8:1) or BC-PDA (4:1) experimental group, the adhesion strength of OHA-CMCS / BC-PDA hydrogel increases with the increase of the added BC-PDA content. This is because with the increase of BC-PDA, more catechol groups can be given to the hydrogel, enhancing adhesion. Secondly, under the same volume of BC-PDA conditions, the adhesion strength of the BC-PDA (4:1) experimental group is higher than that of the BC-PDA (8:1) experimental group, which is also due to more catechol groups on dopamine under the 4:1 condition.
[0135] Furthermore, the SEM test results of the mussel-like self-healing hydrogel dressing are as follows:
[0136] like Fig.10 As shown in the figure, compared with pure OHA-CMCS hydrogel, OHA-CMCS / BC hydrogel enhanced with 20 μL BC has a denser network structure, indicating that BC fibers are evenly distributed in the hydrogel network, giving the hydrogel more and more uniform cross-linking points. The network of the hydrogel enhanced with 20 μL BC-PDA (4:1) is denser than that of the hydrogel enhanced with 10 μL BC-PDA (4:1). This indicates that with the increase of BC-PDA content, the hydrogel network distribution becomes denser.
[0137] Furthermore, in combination with the above mechanical properties and adhesion performance tests, some optimal preparation conditions (OHA-CMCS, 10μL BC-PDA (4:1), 20μL BC-PDA (4:1), 40μL BC-PDA (8:1), 60μL BC-PDA (8:1)) were selected for swelling performance testing. The specific test method for the swelling performance test of the mussel-like adhesion self-healing hydrogel dressing is as follows:
[0138] The hydrogels of different concentrations were immersed in PBS solution and the temperature was set at 37°C. The hydrogels were taken out of PBS every 4 hours to remove the surface water and then weighed and recorded as W. t , the initial weight of the hydrogel is recorded as W 0 , the swelling rate test formula is: swelling rate (%) = W t / W 0 ×100%.
[0139] In this embodiment, the hydrogels prepared under different conditions were immersed in PBS and weighed every 4 hours after removing the surface water. Fig.11 As shown in the figure, the hydrogel began to swell after being immersed in PBS. Compared with the OHA-CMCS self-healing hydrogel (swelling multiple 3.41), the swelling multiples of the mussel self-healing hydrogels with different preparation conditions and different volumes of BC-PDA all increased, which may be due to the introduction of a large number of hydrophilic groups on BC and PDA. At the same time, the swelling multiples decreased with the increase of the added BC-PDA content. The swelling multiples of the self-healing hydrogels with 10μL BC-PDA (4:1), 20μL BC-PDA (4:1), 40μL BC-PDA (8:1) and 60μL BC-PDA (8:1) were 5.55, 5.31, 4.46 and 3.77, respectively. This phenomenon is mainly due to the fact that a large amount of BC-PDA increases its gel cross-linking density. In addition, the structure of DA changes during oxidation and loses its water absorption capacity (the rigid structure of the six-membered ring is destroyed and the hydrophilic hydroxyl group is lost). Simply put, the more solid content in the hydrogel, the higher the cross-linking density and stability. It is difficult for PBS to penetrate into the hydrogel, so the swelling multiple of the high cross-linking density hydrogel is relatively low. The hydrogel material prepared in this experiment has good swelling behavior, can absorb moisture around the wound, keep the wound relatively dry, and maintain the integrity of the wound, which is conducive to clinical application.
[0140] Furthermore, the specific steps of testing the self-healing ability of the mussel-like self-healing hydrogel dressing are as follows:
[0141] like Fig.12 As shown, the hydrogel was cut into two pieces and then put together to observe with the naked eye whether they would change into a complete gel, and the incision was observed with an inverted fluorescence microscope. After 1 minute, the hydrogel began to close, and the incision began to decrease significantly within 5 minutes. After 10 minutes, the incision was almost healed. The results show that OHA-CMCS / BC-PDA hydrogel has good self-healing properties and can be used as a good wound dressing.
[0142] Furthermore, the specific steps of the drug release test of the mussel-mimicking self-healing hydrogel dressing are as follows:
[0143] Weigh 0.1 g of doxycycline hydrochloride powder and add it to the prepared 10 mL OHA solution. Oscillate at room temperature in the dark for 1 h to allow the drug to fully dissolve in OHA. After the drug is fully dissolved, prepare four drug-loaded hydrogels of No. 1, 4, 5, 6, and 7 (stop reaction) according to Table 2;
[0144] 0.1g / mL doxycycline hydrochloride standard solution: Accurately weigh 0.5g of doxycycline hydrochloride standard, transfer to a 5mL volumetric flask after complete dissolution, and make up to volume with deionized water;
[0145] Preparation of standard solutions of different concentrations: dilute the 0.1 g / mL standard solution to 0.05 g / mL, 0.02 g / mL, 0.01 g / mL, 0.005 g / mL, and 0.001 g / mL to obtain standard solutions of different concentrations;
[0146] Drawing of standard curve: Measure the OD value of the above standard solutions of each concentration at 215nm with a UV spectrophotometer, and draw a standard curve with solution concentration as the horizontal axis and OD as the vertical axis;
[0147] The prepared hydrogel was placed in a centrifuge tube containing 2 mL of 0.01Mol / L PBS solution. 1 mL of the solution in the centrifuge tube was aspirated every 30 min, 2 h, 8 h, 20 h, and 24 h. The OD value at a wavelength of 215 nm was measured with a UV spectrophotometer, and 1 mL of PBS was added to the centrifuge tube. The concentration of the drug was calculated from the standard curve, which was the free drug concentration. The drug loading (LC) was obtained by the following formula:
[0148] Drug loading LC (%) = (total drug amount - free drug amount) / gel mass × 100%.
[0149] In this embodiment, Fig.13 It can be seen that at 30 minutes, the cumulative drug release rates of OHA-CMCS, 10μL BC-PDA (4:1), 20μL BC-PDA (4:1), 40μL BC-PDA (8:1) and 60μL BC-PDA (8:1) hydrogels were 11.8%, 11%, 9.7%, 8.1%, and 6.5%, respectively, indicating that the drug release rate decreased after adding BC-PDA, achieving the purpose of sustained release, and as the amount of BC-PDA increased, the network structure of the hydrogel became denser and the drug release rate further decreased. The initial release rate of the drug-loaded hydrogel was high because the drug remained on the surface of the hydrogel during the preparation of the drug-loaded hydrogel. From 30 minutes to 60 minutes, as the hydrogel swelled, the drug slowly diffused from the pores into the buffer solution, achieving the purpose of sustained drug release. The drug release process of the hydrogel basically tends to be flat in about 1 hour, and the equilibrium drug release rates are 14.5%, 13.8%, 11.8%, 9.6%, and 7.9%, respectively.
[0150] Furthermore, the specific test steps for testing the antibacterial ability of the mussel-like adhesion self-healing hydrogel dressing are as follows:
[0151] Use a hole puncher to punch the common filter paper used in the laboratory into discs with a diameter of 0.5 cm, put them in a test tube, seal and sterilize;
[0152] Prepare a suspension of the cultured E. coli at a preset concentration, use a pipette to draw 2 mL of the bacterial suspension into a sterilized culture dish, rotate the culture dish to mix the culture medium and bacterial solution, and let it stand to form a plate;
[0153] Use a pipette to draw 15 μL of sterile water, pick up a piece of filter paper with sterile tweezers, soak the filter paper with sterile water, and gently stick the filter paper on the culture medium as a blank control;
[0154] Use tweezers to pick up the hydrogel and gently stick it on the culture medium. Repeat 3 times for each concentration according to the above method, and use a filter paper soaked in sterile water as a blank control.
[0155] After incubating at an appropriate temperature for a preset time, observe and measure the size of the inhibition zone with a ruler or vernier caliper to calculate the inhibition rate.
[0156] In this embodiment, in order to compare the effect of the added BC-PDA content on the antibacterial properties of OHA-CMCS / BC-PDA hydrogel, three groups of BC-PDA with different ratios (10 μL, 20 μL, 40 μL, and 60 μL) were set to compare their antibacterial properties, and OHA-CMCS hydrogel without BC-PDA was set as a control, as shown in FIG. Fig.14 As shown in the figure, the sizes of the inhibition zones of each hydrogel against E. coli measured with a vernier caliper are OHA-CMCS / BC-PDA (60μL) (18.1mm) > OHA-CMCS / BC-PDA (40μL) (16.4mm) > OHA-CMCS / BC-PDA (20μL) (12.4mm) > OHA-CMCS / BC-PDA (10μL) (11.3mm) > OHA-CMCS (11.3mm). From the above, it can be concluded that as the amount of BC-PDA increases, the antibacterial properties of OHA-CMCS / BC-PDA hydrogel also increase. Studies have shown that polydopamine can encapsulate bacteria and inhibit their growth, so adding a high content of BC-PDA can enhance the antibacterial properties of the hydrogel.
[0157] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.
Claims
1. A method for preparing a mussel-like self-healing hydrogel dressing, characterized in that: The steps include: S1: Synthesis of oxidized hyaluronic acid using hyaluronic acid and sodium periodate; S2: adding dopamine hydrochloride to the bacterial cellulose suspension, adjusting the pH to 12 with sodium hydroxide, and stirring, DA polymerizes in an alkaline environment to obtain a polydopamine-modified bacterial cellulose suspension for use; S3: preparing a self-healing hydrogel by reacting the prepared oxidized hyaluronic acid with carboxymethyl chitosan based on Schiff base; S4: Based on nano-enhancement and mussel-like adhesion mechanism, polydopamine-modified bacterial cellulose was added to the prepared self-healing hydrogel to obtain a mussel-like adhesion self-healing hydrogel dressing; The method for preparing the mussel-mimicking self-healing hydrogel dressing further includes preliminary preparations, which include: Dispersion of bacterial cellulose: accurately weigh 4 g of bacterial cellulose and rinse it with secondary water, cut it into pieces and put it into a 100 mL beaker, add 50 mL of ultrapure water to dissolve it, and use an ultrasonic crusher to crush and disperse it to obtain an 8% w / v BC bacterial cellulose suspension for use; Preparation of 3 mol / L NaOH solution: weigh 12 g of sodium hydroxide solid, dissolve it in secondary water in a beaker, drain it into a 100 mL volumetric flask with a glass rod, dilute to the mark, shake well and set aside; Preparation of 3 mol / L HCL solution: Use a measuring cylinder to measure 25 mL of 36% concentrated hydrochloric acid and pour it into a beaker. Dilute it with distilled water and drain it into a 100 mL volumetric flask with a glass rod and dilute to the mark. Shake well and set aside. Preparation of hydroxylamine hydrochloride-methyl orange solution: weigh 0.025g of methyl orange powder in a beaker and add 50mL of deionized water to dissolve it to obtain a 0.05% w / v methyl orange aqueous solution for later use; accurately weigh 4.34g of hydroxylamine hydrochloride, add 200mL of deionized water to fully dissolve it in a beaker, pour the above beaker solution into a 250mL volumetric flask and add 2.5mL of 0.05% w / v methyl orange aqueous solution and dilute to the scale line for later use.
2. The method for preparing the mussel-like self-healing hydrogel dressing according to claim 1, characterized in that: Step S1 is specifically as follows: Weigh 2 g of hyaluronic acid and dissolve it in 200 mL of deionized water. Stir and dissolve it at 25°C to obtain a 1% w / v hyaluronic acid aqueous solution. Dissolve 1.27 g of sodium periodate in 20 mL of deionized water under light-protected conditions. In a light-proof environment, add sodium periodate aqueous solution dropwise into the hyaluronic acid solution, and react in a light-proof environment at 25°C for 8 hours. Then, add 1 mL of ethylene glycol to the solution and continue stirring for 1 hour to terminate the oxidation reaction. To obtain a pure product, the product was dialyzed for 3 days using a 3.5 KDa dialysis bag and freeze-dried to obtain oxidized hyaluronic acid.
3. The preparation method and testing method of the mussel-like self-healing hydrogel dressing according to claim 2, characterized in that: In step S1, the molar ratio of sodium periodate:hyaluronic acid=1.2:
1.
4. The method for preparing the mussel-like self-healing hydrogel dressing according to claim 3, characterized in that: The specific steps of step S2 are: weighing a preset mass of dopamine hydrochloride and adding it to 10mL of 8% w / v bacterial cellulose suspension, and adjusting the pH to 12 with 3 mol / L sodium hydroxide, stirring with a magnetic stirrer for 1 hour at room temperature, DA polymerizes in an alkaline environment, and obtaining a polydopamine-modified bacterial cellulose suspension for use.
5. The method for preparing the mussel-like self-healing hydrogel dressing according to claim 4, characterized in that: In step S3, the concentration of carboxymethyl chitosan is 4% w / v, and it is transparent and viscous. The concentration of oxidized hyaluronic acid is 10% w / v, and its aqueous solution is transparent and watery.
6. A test method for a mussel-like self-healing hydrogel dressing, applied to the mussel-like self-healing hydrogel dressing prepared by the method for preparing the mussel-like self-healing hydrogel dressing as claimed in claim 5, characterized in that: The test contents include: The hydroxylamine hydrochloride method was used to quantitatively determine the amount of aldehyde groups in the modified hyaluronic acid; Test on gelation time of mussel-mimicking self-healing hydrogel dressing; Mechanical properties testing of mussel-mimicking self-healing hydrogel dressing; Adhesion ability and adhesion strength test of mussel-mimicking self-healing hydrogel dressing; SEM test of mussel-mimicking self-healing hydrogel dressing; Swelling performance test of mussel-mimicking self-healing hydrogel dressing; Testing the self-healing ability of mussel-mimicking self-healing hydrogel dressing; Drug release test of mussel-mimicking self-healing hydrogel dressing; Test of the antibacterial ability of mussel-mimicking self-healing hydrogel dressing.
7. The testing method of the mussel-mimicking self-healing hydrogel dressing according to claim 6, characterized in that: The specific test steps for quantitatively determining the amount of aldehyde groups in modified hyaluronic acid using the hydroxylamine hydrochloride method are as follows: Weigh 0.025 g of methyl orange powder in a beaker and add 50 mL of deionized water to dissolve it to obtain a 0.05% w / v methyl orange aqueous solution for later use; accurately weigh 4.34 g of hydroxylamine hydrochloride and add 200 mL of deionized water to fully dissolve it in a beaker; pour the above beaker solution into a 250 mL volumetric flask and add 2.5 mL of 0.05% w / v methyl orange aqueous solution and dilute to the scale for later use; Weigh 0.1g of oxidized hyaluronic acid (OHA) and add it to 25mL of hydroxylamine hydrochloride-methyl orange solution. Dissolve it under magnetic stirring and leave it for 3h. Titrate it with 0.01mol / L sodium hydroxide solution and it changes from red to yellow. The volume of sodium hydroxide consumed is recorded as V and the blank control is recorded as V0. The oxidation degree and aldehyde content are calculated according to the following formula: Where n NaOH is the molar concentration of NaOH used for titration, in mol / L; W OHA is the mass of the sample measured, in g.
8. The testing method of the mussel-mimicking self-healing hydrogel dressing according to claim 7, characterized in that: The specific test method for the mechanical properties test of the mussel-like self-healing hydrogel dressing is as follows: The compression performance of the mussel-like self-healing hydrogel dressing samples was tested using a universal mechanical machine, and the compression speed was set to 5 mm / min; The stress calculation formula is: The strain calculation formula is: Where Load is the load value, unit is N; position is the displacement, unit is mm.
9. The testing method of the mussel-mimicking self-healing hydrogel dressing according to claim 8, characterized in that: The specific test method for the swelling performance test of the mussel-like self-healing hydrogel dressing is as follows: The hydrogels prepared under different conditions were immersed in a certain amount of PBS solution and the temperature was set at 37°C. The hydrogels were taken out of PBS every 4 hours to remove the surface water and then weighed and recorded as W. t The initial weight of the hydrogel is recorded as W0, and the swelling rate test formula is: swelling rate (%) = W t / W0×100%.
10. The testing method of the mussel-mimicking self-healing hydrogel dressing according to claim 9, characterized in that: The specific test steps for the antibacterial ability test of the mussel-like self-healing hydrogel dressing are as follows: Use a hole puncher to punch the common filter paper used in the laboratory into discs with a diameter of 0.5 cm, put them in a test tube, seal and sterilize; Prepare a suspension of the cultured E. coli at a preset concentration, use a pipette to draw 2 mL of the bacterial suspension into a sterilized culture dish, rotate the culture dish to mix the culture medium and bacterial solution, and let it stand to form a plate; Use a pipette to draw 15 μL of sterile water, pick up a piece of filter paper with sterile tweezers, soak the filter paper with sterile water, and gently stick the filter paper on the culture medium as a blank control; Use tweezers to pick up the hydrogel and gently stick it on the culture medium. Repeat the above method for each sample three times, and use a filter paper soaked in sterile water as a blank control. After incubation at 37°C for a preset time, observe and measure the size of the inhibition zone with a ruler or vernier caliper to calculate the inhibition rate.
Citation Information
Patent Citations
Multifunctional dual-network cross-linked hydrogel wound dressing inspired by mussels
CN116650710A
Hydrogel containing carboxy chitosan and oxidized hyaluronic acid and preparation method thereof
CN118546437A
Hydrogel comprising oxidized polysaccharide and amine-modified hyaluronic acid for wound dressings and manufacturing method thereof
KR1020180052261A
Methods of making chitosan / hyaluronic acid hydrogel compositions and compositions made therefrom
US20210085823A1
Hydrogel compound and use thereof
WO2024120364A1